Titanium Oxysulfate‐Derived 1D Lepidocrocite Titanate Nanostructures - Sukanya Maity; Mohamed Ibrahim; Hussein Badr; Treesa Reji; Mary Q. Hassig; Tongjie Zhang; Christopher Li; Johanna Rosén; Michel W. Barsoum (Advanced Materials Interfaces)
Abstract Nanostructured titania, TiO2, holds significant importance in various scientific fields and technologies for their distinctive properties and multipurpose characteristics. In this article, the facile, economical, and scalable synthesis of 1D lepidocrocite, 1DL, titania nanostructures derived from a water‐soluble Ti precursor, titanium oxysulfate (with oxidation of Ti+4) at temperature <100 °C under atmospheric pressure is discussed. Titanium oxysulfate with tetramethyl ammonium hydroxide, TMAH, is simply reacted to yield individual lepidocrocite titania‐based chain‐forming nanofilaments, NFs, 6 × 6 Å2 in minimal cross‐section and aspect ratios of ≈20 1DLs. If only ethanol is used for washing, the 1DL self‐assemble into ≈10 µm, porous mesostructured particles, PMPs. If water is used, quasi‐2D sheets form instead. Characterization of the resulting powders showed them to be quite similar to those derived from TiB2, and other water‐insoluble Ti precursors. The 1DL bandgap energies are ≈4 eV, due to quantum confinement. They adsorbed rhodamine 6G. The latter also sensitized the 1DLs and allowed for dye degradation using only visible light. Used as electrodes in supercapacitors, the 1DLs can be cycled over 1.6 V and result in high power densities (300 W kg−1). Stronger birefringence started to appear in samples with concentrations >15 gL−1 indicating the formation of a liquid crystal phase. This new synthesis protocol enables the cheaper scalable production of 1DLs with significant implications across various fields.